KEPEMIMPINAN DAN MOTIVASI KERJA SERTA IMPLIKASINYA TERHADAP KINERJA PENYULUH PERTANIAN - Murni, Murni (Universitas Muhammadiyah Makassar, 2012)
Research aim to analysed influence of leadership on employee motivation, and the effect of motivation on the performance ofagricultural extension services in district Takalar. Data collected byquesionary